Immune in myocardial ischemia/reperfusion injury: potential mechanisms and therapeutic strategies - Xuan, Xiaoyu; Fan, Jilin; Zhang, Jingyi; Ren, Ming; Feng, Limin (Frontiers in Immunology, 2025)
Myocardial infarction (MI), which is characterized by high morbidity and mortality, is a serious threat to human life and health, and timely reperfusion therapy to save ischemic myocardium is currently the most effective intervention. Although reperfusion therapy effectively restores coronary blood flow and maximally limits the infarct size, it triggers additional cell death and tissue damage, which is known as myocardial ischemia/reperfusion injury (MIRI). Multiple immune cells are present in the reperfusion area, executing specific functions and engaging in crosstalk during diverse stages, constituting a complex immune microenvironment involved in tissue repair and regeneration after MIRI. Immunotherapy brings new hope for treating ischemic heart disease by modulating the immune microenvironment. In this paper, we explore the regulatory roles of various immune cells during MIRI and the close relationship between different cell deaths and the immune microenvironment. In addition, we present the current status of research on targeting the immune system to intervene in MIRI, with the expectation of providing a basis for achieving clinical translation.